Fire & Blood - Martin, George R. R.; Wheatley, Doug (New York Bantam Books, 2018)
This is the first volume of the definitive two-part history of the Targaryens in Westeros and covers Aegon I (the Conqueror) to the regency of Aegon III (the Dragonslayer). House Targaryen was the only family of dragonlords to survive the Doom of Valyria, and took up residence on Dragonstone. Re-hear tales of the legendary Aegon the Conqueror, creator of the Iron Throne. Meet the generations of Targaryens who fought to hold that iconic seat, from Aegon the Conqueror all the way up to the civil war that nearly tore their dynasty apart. What really happened during the Dance of the Dragons? Why was it so deadly to visit Valyria after the Doom? What were Maegor the Cruel's worst crimes? What was it like in Westeros when dragons ruled the skies? These are but a few of the questions answered by a learned maester of the Citadel. Discover the often bloody history of Westeros when dragons ruled the skies.
Keywords: Targaryen, House of -- (Fictitious family) -- Fiction; Westeros (Imaginary place) -- Fiction; Imaginary places -- Fiction; Imaginary wars and battles -- Fiction; Monarchy -- Fiction; Kings and rulers, Medieval -- Fiction; Kings and rulers, Medieval -- Fiction -- Succession; Royal houses -- Fiction; Knights and knighthood -- Fiction; Magic -- Fiction; Dragons -- Fiction; Knights and knighthood -- Fiction; Dragons -- Fiction; Fantasy; FICTION / Fantasy / Epic; FICTION / Action & Adventure; FICTION / Fantasy / Dragons & Mythical Creatures; Epic fiction; Fantasy fiction; Novels; Fantasy fiction; Fantasy fiction